Yiqi Juanshen decoction alleviates renal interstitial fibrosis by targeting the LOXL2/PI3K/AKT pathway to suppress EMT and inflammation - Kaiyue Tan; Jingwei Deng; Yi Liu; Yudi Zhang; Yu Xiong; Su Yuan; Jun Liu; Zhiwei Chen; Yuanyuan Liu; Wenfu Cao (Scientific Reports)
Abstract Chronic kidney disease (CKD) is a major health concern, with renal interstitial fibrosis (RIF) as a key feature. Effective management of RIF is crucial for treating CKD. Yiqi Juanshen decoction (YQJSD), as traditional Chinese medicine, has shown promising results in CKD treatment. This study evaluates YQJSD’s effectiveness in ameliorating RIF and explores the underlying molecular mechanisms using the unilateral ureteral obstruction (UUO) model. YQJSD has been shown to effectively reduce serum creatinine and blood urea nitrogen levels, decrease extracellular matrix deposition, and down-regulate the expression of α-SMA, COL4α1, Fibronectin (FN). Mechanistically, YQJSD exerts its effects by modulating multiple pathways: it inhibits the NF-κB signaling pathway, inhibiting the expression of pro-inflammatory cytokines like NF-κB1, IL-1β, TNF-α, and CCR1. Simultaneously, YQJSD suppresses the epithelial-mesenchymal transition (EMT) by downregulating the expression of Snail1, Vimentin, Twist1, and FSP1, while increasing E-cadherin expression. Moreover, YQJSD can regulate the PI3K/AKT signaling pathway by decreasing the expression of LOXL2 and PIK3R1, along with p-AKT1/2/3. This modulation of the LOXL2/PI3K/AKT pathway contributes to the inhibition of both EMT and inflammation, highlighting a critical role in the therapeutic intervention against RIF. These findings suggest that YQJSD may serve as a promising therapeutic management of RIF in CKD patients.